Researches of the assortment of drugs for the treatment of diabetes II type оn the pharmaceutical market of Ukraine - I. V. Kovalevska; O. A. Ruban; O. M. Yevtushenko (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Type II diabetes is a global pandemic, as evidenced by data from a study by the International Diabetes Federation. The disease is a chronic, progressive process with a special metabolic condition that is characterized by hyperglycemia. Therapeutic effects should be aimed at eliminating the main causes of type II diabetes mellitus: insulin secretion dysfunction, a decrease in tissue resistance to insulin, or a combination of these. The aim of the work was to study the range of oral antidiabetic drugs on the pharmaceutical market of Ukraine for the treatment of type II diabetes. The objects of study were drugs used in the treatment of type II diabetes. Studies were conducted using content analysis of official sources of information. In the course of the work, the range of antidiabetic drugs, classification, mechanism of action, cost, main advantages and disadvantages of use were established. It is established that the most common dosage form for the treatment of diabetes are tablets, which occupy more than 90% of the total range of drugs. The lack of modern types of dosage forms in the group A10B is the basis for the creation of new drugs with improved biopharmaceutical and consumer properties. The data obtained indicate a strong dependence of the pharmaceutical market of antidiabetic drugs of Ukraine on imports, with the exception of insulin (А10В). The share of imports in the market in quantitative terms for the period under review amounted to more than 75.86% of the total market volume. It has been established that the use of drugs of the A10B A, A10B F groups with an affordable cost with active therapy contributes to a lower rate of development of diabetes mellitus type II and a high degree of regression to normal glucose, without affecting the fluctuations in body weight. Preparations of the new generation (A10B H, A10B J, A10B X) are highly effective with an insufficient safety profile. The high cost of drugs of these groups makes them inaccessible to the general population. It has been shown that only metformin and voglibosis have a positive effect on body mass fluctuation rates, which will ensure safe and effective glycemic control with minimal risk of hypoglycemia and without weight gain in the treatment of type II diabetes.